The Evaluation of Coal Mine Safety Based on Entropy Method and Mutation Theory. Issue 3 (May 2021) - Mi, Xin; Cao, Qinggui; Li, Dan; Wang, Junqing
Abstract: In order to accurately evaluate the safety status of coal mines and improve the safety level of coal mines, the method of evaluating the state of coal mine safety combined with entropy method and mutation theory is proposed. By analyzing the influence factors of coal mine safety status, 17 evaluation indicators were established from the four aspects of employee quality, equipment facilities, natural conditions and safety management, and the evaluation index system of coal mine safety status was established. Based on this evaluation model and process, the safety status evaluation and analysis of the example coal mine are carried out, and the evaluation results are consistent with the actual safety status of the coal mine, which confirms the reasonable feasibility of the evaluation method. This method can be used to evaluate the safety status of coal mine and provide the basis for the formulation of safety countermeasures.